Fall detection using accelerometer-based smartphones: Where do we go from here? - Stampfler, Tristan; Elgendi, Mohamed; Fletcher, Richard Ribon; Menon, Carlo (Frontiers in Public Health, 2022)
According to World Health Organization statistics, falls are the second leading cause of unintentional injury deaths worldwide. With older people being particularly vulnerable, detecting and reporting falls have been the focus of numerous health technology studies. We screened 267 studies and selected 15 that detailed pervasive fall detection and alerting apps that used smartphone accelerometers. The fall datasets used for the analyses included between four and thirty-eight participants and contained data from young and old subjects, with the recorded falls performed exclusively by young subjects. Threshold-based detection was implemented in six cases, while machine learning approaches were implemented in the other nine, including decision trees, k-nearest neighbors, boosting, and neural networks. All methods could ultimately achieve real-time detection, with reported sensitivities ranging from 60.4% to 99.3% and specificities from 74.6% to 100.0%. However, the studies had limitations in their experimental set-ups or considered a restricted scope of daily activities—not always representative of daily life—with which to define falls during the development of their algorithms. Finally, the studies omitted some aspects of data science methodology, such as proper test sets for results evaluation, putting into question whether reported results would correspond to real-world performance. The two primary outcomes of our review are: a ranking of selected articles based on bias risk and a set of twelve impactful and actionable recommendations for future work in fall detection.